Trabecular bone microstructure is impaired in the proximal femur of human immunodeficiency virus-infected men with normal bone mineral density - Kazakia, Galateia J.; Carballido-Gamio, Julio; Lai, Andrew; Nardo, Lorenzo; Facchetti, Luca; Pasco, Courtney; Zhang, Chiyuan A.; Han, Misung; Parrott, Amanda Hutton; Tien, Phyllis; Krug, Roland (Quantitative Imaging in Medicine and Surgery; Vol 8, No 1 (February 27, 2018): Quantitative Imaging in Medicine and Surgery (Imaging and Diagnostics of Osteoporosis and Sarcopenia Special Issue), 2017)
Background: There is evidence that human immunodeficiency virus (HIV) infection and antiretroviral therapy (ART) are independent risk factors for osteoporosis and fracture which is not solely explained by changes in bone mineral density. Thus, we hypothesized that the assessment of trabecular microstructure might play an important role for bone quality in this population and might explain the increased fracture risk. In this study, we have assessed bone microstructure in the proximal femur using high-resolution magnetic resonance imaging (MRI) as well as in the extremities using high resolution peripheral quantitative computed tomography (HR-pQCT) in HIV-infected men and healthy controls and compared these findings to those based on areal bone mineral density (aBMD) derived from dual X-ray absorptiometry (DXA) which is the standard clinical parameter for the diagnosis of osteoporosis. Methods: Eight HIV-infected men and 11 healthy age-matched controls were recruited and informed consent was obtained before each scan. High-resolution MRI of the proximal femur was performed using fully balanced steady state free precession (bSSFP) on a 3T system. Three volumes of interest at corresponding anatomic locations across all subjects were defined based on registrations of a common template. Four MR-based trabecular microstructural parameters were analyzed at each region: fuzzy bone volume fraction (f-BVF), trabecular number (Tb.N), thickness (Tb.Th), and spacing (Tb.Sp). In addition, the distal radius and distal tibia were imaged with HR-pQCT. Four HR-pQCT-based microstructural parameters were analyzed: trabecular bone volume fraction (BV/TV), Tb.N, Tb.Th, and Tb.Sp. Total hip and spine aBMD were determined from DXA. Results: Microstructural bone parameters derived from MRI at the proximal femur and from HR-pQCT at the distal tibia showed significantly lower bone quality in HIV-infected patients compared to healthy controls. In contrast, DXA aBMD data showed no significant differences between HIV-infected patients and healthy controls. Conclusions: Our results suggest that high-resolution imaging is a powerful tool to assess trabecular bone microstructure and can be used to assess bone health in HIV-infected men who show no differences to healthy males by DXA aBMD. Advances in MRI technology have made microstructural imaging at the proximal femur possible. Further studies in larger patient cohorts are clearly warranted.